2011
DOI: 10.1111/j.1365-2044.2011.06764.x
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of the dose-response of caudal methylprednisolone with levobupivacaine in chronic lower back pain*

Abstract: SummaryThe question as to what constitutes the ideal epidural steroid injection remains unresolved. We performed a prospective, randomised, double-blind, AB ⁄ BA 2 · 2 crossover study of caudal 40 vs 80 mg methylprednisolone acetate (in 20 ml levobupivacaine 0.125%) in outpatients with chronic low back pain. Data from 33 participants were analysed. The Oswestry Disability Index improved in both dose groups over time following injection. However, a statistically significant improvement was only observed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 26 publications
2
34
0
Order By: Relevance
“…In high-risk patients (e.g., patients with previous surgery) and procedures (e.g., cervical and thoracic transforaminal ESI) in which the inadvertent intravascular injection of depo-steroids can have catastrophic consequences such as paralysis and death, [117][118][119] physicians might consider removing steroids from the injectate and using nonsteroid solutions as a first-line treatment. Using nonsteroid solutions may also reduce the risk of rare but potentially fatal complications such as meningitis, which has recently been attributed to a contaminated steroid batch.# On the basis of these results and the results of other clinical trials demonstrating no differences between high-and lowdose ESI [110][111][112]120 the dose of steroids may be considerably reduced or even eliminated in high-risk patient populations. Examples of these patients might include individuals at high risk for avascular necrosis, 121 and those with diabetes, 122 at high risk for infection, 123 poor wound healing, or in whom the temporary suppression of the adrenocortical axis could adversely affect outcomes (e.g., those scheduled for major surgery).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…In high-risk patients (e.g., patients with previous surgery) and procedures (e.g., cervical and thoracic transforaminal ESI) in which the inadvertent intravascular injection of depo-steroids can have catastrophic consequences such as paralysis and death, [117][118][119] physicians might consider removing steroids from the injectate and using nonsteroid solutions as a first-line treatment. Using nonsteroid solutions may also reduce the risk of rare but potentially fatal complications such as meningitis, which has recently been attributed to a contaminated steroid batch.# On the basis of these results and the results of other clinical trials demonstrating no differences between high-and lowdose ESI [110][111][112]120 the dose of steroids may be considerably reduced or even eliminated in high-risk patient populations. Examples of these patients might include individuals at high risk for avascular necrosis, 121 and those with diabetes, 122 at high risk for infection, 123 poor wound healing, or in whom the temporary suppression of the adrenocortical axis could adversely affect outcomes (e.g., those scheduled for major surgery).…”
Section: Discussionmentioning
confidence: 83%
“…In addition to the evidence presented here, several other randomized studies indirectly bolster this assertion. Randomized, doubleblind studies comparing high doses of steroid with lower doses in which the steroid was replaced by saline 110,111 or local anesthestic 112 have consistently failed to demonstrate any significant differences between treatment groups. A systematic review by Rabinovitch et al 113 found a statistically significant benefit for larger epidural injectate volumes irrespective of the contents, suggesting that the beneficial effect of nonsteroid solutions may counterbalance dilution of steroids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Members of the study team obtained written informed consent from all study participants prior to randomization in accordance with the ethical principles that have their origin in the Declaration of Helsinki and the ICH (International Conference on Harmonisation) Guideline for Good Clinical Practice. Full details of the trial’s organization and its clinical findings have been published elsewhere [20]. …”
Section: Methodsmentioning
confidence: 99%